Efficacy of Probiotics in Reducing Relapse in Ulcerative Colitis: A Meta-Analysis of Controlled Trials - Wajih Ul Hassan,; Somaraj, Meghna; Nipu, Airin Parvin; Nadeem, Najwa; Zahra, Aania; Mariam, Bibi; Islam, Samreen; Farooq, Addan; Shaikh, Maham (Indus Journal of Bioscience Research, 2025)
Background: Ulcerative colitis (UC) is a chronic inflammatory bowel disease marked by periods of remission and relapse. While mesalazine remains a standard maintenance therapy, long-term use may lead to adverse effects. Probiotics, known to modulate gut microbiota and reduce intestinal inflammation, have emerged as a potential adjunct or alternative treatment to prevent relapse in UC. Objective: This meta-analysis aimed to evaluate the efficacy of probiotics compared to mesalazine in maintaining remission and reducing relapse rates in UC patients. Methods: A systematic search of PubMed, Embase, Scopus, and Cochrane CENTRAL was conducted to identify randomized controlled trials (RCTs) from 1990 to 2023 that compared probiotics with mesalazine in adult UC patients. Studies were screened based on predefined inclusion criteria. Data were extracted and pooled risk ratios (RRs) were calculated using a random-effects model. Heterogeneity was assessed using I² statistics, and risk of bias was evaluated via the Cochrane RoB 2.0 tool. Results: Four RCTs involving 533 patients were included. Among them, 264 received probiotic therapy and 269 received mesalazine. The pooled RR for relapse was 0.97 (95% CI: 0.79–1.20; p = 0.80), indicating no statistically significant difference between groups. Subgroup analysis at 12-month follow-up showed similar outcomes (RR = 0.96; 95% CI: 0.77–1.19; p = 0.68). Heterogeneity was low (I² = 0%). Conclusion: Probiotic therapy demonstrates comparable efficacy to mesalazine in preventing relapse in UC patients. Given their favorable safety profile and patient acceptability, probiotics may serve as a viable maintenance strategy, warranting further large-scale studies to confirm long-term outcomes.